The history of orchestration - Carse, Adam (Dover Publications, 1964)
Author Adam Carse examines the evolution of individual musical instruments along with varying performance techniques and concepts of instrumental color. He further explores the recognition of major instrumental groups and their musical distinctions, decisions regarding volume and balance of tone, the influence of musical subject matter upon orchestration, and many similar topics. This volume represents a splendid resource for music students, enthusiasts of musical history and classical music, and music lovers of all ages.